Developing Creativity Through Enhanced Communication and Teamwork in Engineering - Frederick Burrack (Educational Considerations, 2020)
Engineers need to address problems through multiple lenses and consider solutions that stray from the most efficient linear consideration. In higher-education training of future engineers, bringing together learning experiences from the liberal arts into learning processes for engineering can enhance the development of creativity and communication skills, and expand conceptions of teamwork. To prepare future generations of engineers, it has been found that experimentation with curricula that intersects educational areas outside of engineering can enhance student competence in ways that is useful to their future success. This study explored intersecting electrical engineering curriculum with creative arts, specifically music composition. Exposure to creative problem-solving processes involved: (a) considering creative alternatives that might generate improved outcomes; (b) deliberation of others’ ideas about the problem-solving process; and (c) recognition that effective communication requires consideration of another’s beliefs, understandings and intentions, as well as flexibility within these considerations.
Keywords: creativity; communication skills; teamwork; interdisciplinary; engineering